Melting and phase diagram of Au–Co alloy at nanoscale by thermodynamic modeling and key experiments. (September 2022) - Zhang, C.; Wan, Y.; Liang, X.H.; Rong, M.H.; Ma, G.T.; Li, L.; Hu, C.H.; Tang, Chengying
Abstract: Au–Co nanoparticles (NPs) were prepared by water-phase chemical reduction method with metal precursor. The samples were coated with silica by Stöber method and characterized by ultraviolet and visible spectrophotometer (UV–vis), transmission electron microscopy (TEM) to obtain the absorption spectrum, size, composition distribution of the nanoparticles. The melting behaviors of the prepared Au8 Co2 NPs and Au6 Co4 NPs were examined by differential scanning calorimetry (DSC). It was observed by DSC measurements that two endothermic effects existed in range of 700.0 K–1350.0 K, corresponding to the melting temperatures of the nanoparticles and the bulk Au–Co alloys, respectively. The surface tension, surface segregation and surface energy of Au–Co NPs of particle size and temperature were calculated by the Butler's equation. On the basis of the obtained experimental results and the Gibbs free energy contributed by surface effects of pure elements and alloys at nanoscale, the nanophase diagrams of Au–Co system with various sizes were optimized. It was indicated that the calculated nanophase diagrams were in good agreement with the experimental results. The calculated eutectic temperatures decreased with the decrease of the size. Highlights: The phase diagrams of Au–Co nanoalloys were thermodynamically investigated. The silica coated Au8 Co2 and Au6 Co4 nanoalloys were prepared and their thermodynamic melting behavior was measured. A self-consistent thermodynamic data set including the size effect was obtained. The calculated Au–Co nano phase diagrams agreed well with experimental data.